Mutational analysis of N-glycosylation recognition sites on the biochemical properties of Aspergillus kawachii α- l-arabinofuranosidase 54 - Koseki, Takuya; Miwa, Yozo; Mese, Yuichiro; Miyanaga, Akimasa; Fushinobu, Shinya; Wakagi, Takayoshi; Shoun, Hirofumi; Matsuzawa, Hiroshi; Hashizume, Katsumi (Biochimica et biophysica acta, 2006)
A role for N-linked oligosaccharides on the biochemical properties of recombinant α- l-arabinofuranosidase 54 (AkAbf54) defined in glycoside hydrolase family 54 from Aspergillus kawachii expressed in Pichia pastoris was analyzed by site-directed mutagenesis. Two N-linked glycosylation motifs (Asn 83–Thr–Thr and Asn 202–Ser–Thr) were found in the AkAbf54 sequence. AkAbf54 comprises two domains, a catalytic domain and an arabinose-binding domain classified as carbohydrate-binding module 42. Two N-linked glycosylation sites are located in the catalytic domain. Asn 83, Asn 202, and the two residues together were replaced with glutamine by site-directed mutagenesis. The biochemical properties and kinetic parameters of the wild-type and mutant enzymes expressed in P. pastoris were examined. The N83Q mutant enzyme had the same catalytic activity and thermostability as the wild-type enzyme. On the other hand, the N202Q and N83Q/N202Q mutant enzymes exhibited a considerable decrease in thermostability compared to the glycosylated wild-type enzyme. The N202Q and N83Q/N202Q mutant enzymes also had slightly less specific activity towards arabinan and debranched arabinan. However, no significant effect on the affinity of the mutant enzymes for the ligands arabinan, debranched arabinan, and wheat and rye arabinoxylans was detected by affinity gel electrophoresis. These observations suggest that the glycosylation at Asn 202 may contribute to thermostability and catalysis.